Effects of Self-Regulation Program on Self-Management Behaviors using Telehealth in Older Adults with Uncontrolled Type 2 Diabetes Mellitus - Vasuri, Awasda; Wirojratana, Virapun; Watanakijkrilert, Doungrut; Assantachai, Prasert (Journal of The Royal Thai Army Nurses, 2024)
This randomized controlled trial aimed to study the effects of self-regulation program on self-management behaviors in older adults with uncontrolled type 2 diabetes mellitus. A total of 40 study participants who received treatments at primary care units at Siriraj Hospital and nearby community, Bangkok, Thailand were recruited according to inclusion criteria and randomly assigned to control and experimental groups, 20 study participants per group. The experimental group received normal nursing care and the self-regulation program covered 12 weeks by using telehealth via ZOOM application in weeks 1 and 2, and had follow-up telephone visits in weeks 3, 5, 7, 9, and 11. The control group received normal nursing care. The pretest and posttest assessments of self-management behaviors of older adults with type 2 diabetes mellitus was conducted in weeks 1 and 12. Chi-square Test, T-Test, and ANCOVA were used for data analysis. The results showed that before the self-regulation program took place, the mean scores of self-management behaviors in the control and experimental groups were not different. After the self-regulation program was completed in week 12, the mean score of self-management behaviors in the experimental group was significantly higher than the mean score in the control group (p < .05). The results suggest that self-regulation program by using telehealth via ZOOM application could help older adults with uncontrolled type 2 diabetic mellitus to improve self-management behaviors.